Does children’s voice matter? Exploring teachers’ and pupils’ perspectives on critical pedagogy in childhood development - Ernest Nyamekye; Seth Asare-Danso; Emmanuel Amo Ofori (Discover Education)
Abstract Current educational reforms in Africa aim to cultivate problem-solving and critical-thinking skills among early childhood learners through a democratic educational approach. Ghana’s newly adopted standards-based curriculum prioritizes the constructivist theory of learning which, among other aims, seeks the development of children’s critical thinking skills and their ability to critique existing knowledge. Critical pedagogy proves to be an educational approach capable of empowering students in this regard. Hence, this study investigated teachers’ and pupils’ perspectives on the role of critical pedagogy in achieving these educational aims. Employing an exploratory case study design, 12 teachers and 20 pupils in four public elementary schools in Sunyani-West Municipal were involved in this inquiry. The study revealed that teachers hardly embraced critical pedagogy. They viewed this educational approach as a threat to their authority and a potential instigator of disobedience among pupils. Conversely, pupils perceived themselves as lacking the right to critique societal norms due to established traditions. Moreover, the political culture of Ghana was cited as one of the major reasons teachers frown upon critical pedagogy in early childhood development. Based on these insights, recommendations for policy and practice have been offered for consideration.